2015
DOI: 10.1007/s10310-015-0488-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of sprouting in the exotic treeRobinia pseudoacaciaL. in Hokkaido, northern Japan

Abstract: Robinia pseudoacacia L., one of the major invasive tree species in Japan, has been used for coppice wood production worldwide. However, we have little knowledge of the species' sprouting characteristics. Here, we tested seasonality in R. pseudoacacia sprout development. We removed aboveground parts of R. pseudoacacia at different times throughout the year (spring, summer, autumn, and winter) and censused sprout demographics for three consecutive growing seasons thereafter. The most vigorous sprouting was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…Therefore, it can be concluded that explants derived from basal and near-basal parts of the mother plant are considerably more appropriate initial explants for in vitro rejuvenation and multiplication. Similar to our results, previous studies using other plant species showed that the source of the explants plays a pivotal role in successful in vitro rejuvenation [ 26 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it can be concluded that explants derived from basal and near-basal parts of the mother plant are considerably more appropriate initial explants for in vitro rejuvenation and multiplication. Similar to our results, previous studies using other plant species showed that the source of the explants plays a pivotal role in successful in vitro rejuvenation [ 26 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 92%
“…We have frequently found severe problems in plant communities where R. psudoacacia was introduced. This species is highly invasive, and its escape from its original planted site threatens the native forest vegetation in Japan (Masaka et al, 2015; Sakio, 2009; Yamada & Masaka, 2007). Recent global climate changes such as the increase in wildfires in central Europe or the frequency of typhoons in East Asia are creating large areas of disturbed land, and consequently providing R. psudoacacia trees many chances to invade other areas in the forests (Koike et al, 2009; Nicolescu et al, 2020; Puchałka et al, 2021; Sakio, 2009; Vítková et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…N N 萌芽により群落を拡大することが知られている 6) 。根萌芽に は,若い根から恒常的に発生して個体の分布を拡大させるも ののほか 6, 11) ,地上部の伐採等の攪乱によって発生するもの もある 13) 。 海岸マツ林に生育しているニセアカシアの場合,根萌芽の 発生のほとんどは水平根の伸長に伴う恒常的なものであると されているが 6) 表-2 全詳細調査区における損傷タイプ別の水平根の総本数 Table 2 The total number of horizontal roots in each damaged class in the minute observation plots…”
unclassified